Floral and genetic divergence across environmental gradients is moderated by inter-population gene flow in Platanthera dilatata (Orchidaceae) - Wallace, Lisa E.; Bowles, Marlin L. (Frontiers in Ecology and Evolution, 2023)
Understanding how natural selection acts on intraspecific variation to bring about phenotypic divergence is critical to understanding processes of evolutionary diversification. The orchid family is well known for pollinator-mediated selection of floral phenotypes operating among species and along environmental or geographic gradients. Its effectiveness at small spatial scales is less understood, making the geographic scale at which intraspecific floral variation is examined important to evaluating causes of phenotypic divergence. In this study, we quantified phenotypic variation in the orchid Platanthera dilatata across 26 populations in coastal Southeast Alaska and compared this to edaphic and genetic variation at microsatellite loci. We sought to determine (1) if flower morphological variation is structured at smaller geographic scales, (2) the extent of genetic divergence in relation to phenotypic divergence, (3) the scale at which inter-population gene flow occurs, and (4) the relative importance of geographic distance and abiotic factors on population genetic structure. Two morphological groups were found to separate based on lip and spur length and are restricted to different habitats. Small-flowered forms occur in muskeg bogs, whereas large-flowered forms occur in fens and meadows, and rarely in sub-alpine habitat. Genetic analyses were concordant with the morphological clusters, except for four small-flowered populations that were genetically indistinguishable from large-flowered populations and considered to be introgressed. In fact, most populations exhibited some admixture, indicating incomplete reproductive isolation between the flower forms. Pollinators may partition phenotypes but also facilitate gene flow because short-tongued Noctuidae moths pollinate both phenotypes, but longer-tongued hawkmoths were only observed pollinating the large-flowered phenotype, which may strengthen phenotypic divergence. Nevertheless, pollinator movement between habitats could have lasting effects on neutral genetic variation. At this small spatial scale, population genetic structure is only associated with environmental distance, likely due to extensive seed and pollinator movement. While this study corroborates previous findings of cryptic genetic lineages and phenotypic divergence in P. dilatata, the small scale of examination provided greater understanding of the factors that may underlie divergence.